WARNA YANG MENIPU, REMPAH YANG MENGOBATI: RESIKO MINUMAN BERPEWARNA DAN INOVASI MINUMAN HERBAL UNTUK MENJAGA FUNGSI GINJAL - Lidia Klorida Br Barus; Chindy Umaya; Puji Lestari; Sardamai Laia; Bunga Mari Sembiring (INSTITUT KESEHATAN DELI HUSADA, 2026)
The consumption of colored beverages containing synthetic dyes, artificial sweeteners, and high sugar levels among adolescents has the potential to cause health problems, including kidney function disorders. This Community Service Program entitled “Deceptive Colors, Healing Spices: The Risks of Colored Beverages and Herbal Drink Innovations to Maintain Kidney Function” aimed to increase students’ knowledge about the dangers of colored beverages and encourage healthier consumption patterns through natural herbal drinks. The activity was conducted at SMAS Yapim Biru-Biru involving 11th-grade students through health education, interactive discussions, visual media presentations, and herbal drink-making demonstrations. The results showed an improvement in students’ knowledge and awareness regarding the importance of maintaining kidney health and the benefits of herbal drinks such as turmeric, red ginger, lemongrass, and honey as healthier beverage alternatives.